História natural da hepatite crónica pelo vírus da hepatite B - Areias, J. (1995)
Chronic hepatitis is an etiologically diverse syndrome that may be precipitated by hepatitis B vírus (HBV). Chronic hepatitis B vírus (HVB) is a world-wide health problem. More than 300 millions persons are chronically infected with this vírus. Chronic hepatitis B is a serious disorder that may lead to cirrhosis, hepatic failure, and hepatocellular car cinoma. Chronic hepatitis is defined by biochemical ( ele vated serum aminotransferase levels) or clinical evidence of liver disease of at least 6 months duration, and liver biopsy confirmation of unresolving hepatic inflammation.